Pacing and hazard score of elite open water swimmers during a 5-km indoor pool race - Baldassarre, R.; Ieno, C.; Bonifazi, M.; Piacentini, M. F. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The sensation of fatigue experienced at a certain point of the race is an important factor in the regulation of pacing. The rating of perceived exertion (RPE) is considered one of the main mediators utilized by athletes to modify pacing. The aim was to analyze the relationship between pacing and RPE of elite open water swimmers during national indoor pool championships.